Potret Perempuan pada Film Cinderella (2015) dan Cinderella (2021): Sebuah Kajian Sastra Bandingan - Laily Raff Firdausy (Jurnal Pendidikan Bahasa dan Sastra, 2023)
Cinderella is a well-known literature which tells the story of a girl who suffers from living with her mother and stepsisters, then finds love and happiness by meeting the prince. This romance story filled with magic, loved by various groups, and thanks to its popularity, this story has been adapted several times for the big screen. Each story adaptation certainly has differences. This also applies to the film "Cinderella" which was released in 2015 with the latest "Cinderella" film released in 2021. The biggest difference appears in the aspect of gender, especially regarding how women are portrayed in the two films. After doing a comparison, it was found that the film “Cinderella (2021)” contains many feminist aspects that were not shown in the previous films. Among them is the main character Ella who dares to do business in a social group that looks down on women, as well as the character Gwen, a princess who replaces the prince to become the successor to the royal throne. This, of course influenced by the mindset development of society in the current modern era where gender equality is upheld.